1984
DOI: 10.1016/0092-8674(84)90005-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transferrin recycling in mitotic and interphase hela cells by quantitative fluorescence microscopy

Abstract: Recent findings suggest that membrane vesicle transport during mitosis may be generally inhibited. To test this, we examined the kinetics of uptake and exocytosis of RITC-transferrin in mitotic and interphase HeLa cells. We used quantitative image-intensification fluorescence microscopy to analyze the content of ligands in single cells. This technique was validated by comparison of 3H or RITC-transferrin release from interphase cells determined by microscopy or radiometry. Both methods gave a t1/2 of release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 21 publications
5
60
0
Order By: Relevance
“…As expected, the receptor, which contains a YXXΦ sorting motif was regulated in the same way as the CD8-YAAL reporter. Our transferrin uptake experiments confirmed many previous reports of reduced transferrin uptake during mitosis (7,11,15,22,36,37). Staining of surface TfR indicated that it was abundant at the cell surface during all stages of the cell cycle in HeLa cells.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As expected, the receptor, which contains a YXXΦ sorting motif was regulated in the same way as the CD8-YAAL reporter. Our transferrin uptake experiments confirmed many previous reports of reduced transferrin uptake during mitosis (7,11,15,22,36,37). Staining of surface TfR indicated that it was abundant at the cell surface during all stages of the cell cycle in HeLa cells.…”
Section: Discussionsupporting
confidence: 80%
“…Further studies demonstrated that uptake of fluorescent dextran ceases during mitosis and also confirmed the timing of shutdown to be in early prophase (7). Many other studies went on to confirm and further develop the theory of mitotic shutdown of endocytosis, showing that it is temporary and resumes in telophase (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The reason for shutdown is unclear (18,19), but one recent idea is that "moonlighting" functions for endocytic proteins during mitosis may contribute to the inhibition (20,21).…”
mentioning
confidence: 95%
“…Multiple steps in the transfer of the growing GAG chains through the Golgi apparatus are probably affected. Such transfers are believed to occur by membrane vesicles, and a defect in their capacity to fuse with Golgi membrane, as Warren points out (42), would represent the functional equivalent of the failure to form endocytic vesicles (1, 2), to discharge secretory vesicles (9), or recycle receptors (35,41). All vesicle-mediated transport would appear to be inhibited during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a general cessation of membrane traffic (Warren, 1985, including inhibition of the endocytic pathway as first described by Fawcett (1965). Both invagination of coated pits (Berlin et al, 1978;Pypaert et al, 1987) and recycling of receptors to the cell surface (Sager et al, 1984;Warren et al, 1984) are blocked. From these observations it can be inferred that fusion between endocytic vesicles is also inhibited in mitotic cells.…”
Section: Introductionmentioning
confidence: 99%